Immunogenicity and reactogenicity of the human rotavirus vaccine, RIX4414 oral suspension, when co-administered with routine childhood vaccines in Chinese infants. Issue 3 (3rd March 2016) - Li, Rong-cheng; Huang, Teng; Li, Yanping; Wang, Lao-Hong; Tao, Junhui; Fu, Botao; Si, Guoai; Nong, Yi; Mo, Zhaojun; Liao, XueYan; Luan, Ivy; Tang, Haiwen; et al.
Abstract: This study evaluated the immunogenicity of the human rotavirus (RV) vaccine (RIX4414) when co-administered with routine childhood vaccines in Chinese infants (NCT01171963). Healthy infants aged 6–16 weeks received 2 doses of either RIX4414 or placebo according to a 0, 1-month schedule. Infants received routine diphtheria-tetanus-acellular pertussis (DTPa) and oral poliovirus (OPV) vaccines either separately from or concomitantly with RIX4414/placebo (separate and co-administration cohorts, respectively). Anti-RV IgA seroconversion rates (one month post-dose-2) and seropositivity rates (at one year of age) were measured using ELISA. Immune responses against the DTPa and OPV antigens were measured one month post-DTPa dose-3 in the co-administration cohort. Solicited local and general symptoms were recorded for 8-days post-vaccination (total cohort). The according-to-protocol immunogenicity population included 511 infants in the separate cohort and 275 in the co-administration cohort. One month post-RIX4414 dose-2, anti-RV IgA seroconversion rates were 74.7% (95% confidence interval [CI]: 68.9–79.9) and 64.2% (95% CI: 55.4–72.3) in the separate and co-administration cohorts; seropositivity rates at one year of age were 71.5% (95% CI: 65.5–77.1) and 50.0% (95% CI: 40.9–59.1), respectively. One month post-DTPa dose-3, all infants in the co-administration cohort were seroprotected against diphtheria and tetanus, and seropositive for pertussis toxoid, pertactin and filamentous haemaglutinin. Two months post-OPV dose-3, seroprotection rates against anti-poliovirus types 1, 2 and 3 were >99% in the co-administration cohort. Reactogenicity profiles were similar in both cohorts. RIX4414 was immunogenic and well-tolerated in Chinese infants and did not appear to interfere with the immunogenicity and reactogenicity of co-administered routine childhood vaccines.